Pengembangan Aplikasi Mobile Muhasabah Untuk Evaluasi Diri Harian Berbasis Kotlin Android Dengan Pendekatan Self-Assessment - Raafi Hilmi; Mulia Rahmayu (Jurnal Sains dan Teknologi Informasi, 2026)
Self-reflection (muhasabah) is crucial for fostering self-awareness and improving one’s quality of life, yet it has not become a daily habit—particularly among younger generations. Limited awareness, time constraints, and the lack of practical digital tools are key obstacles. This study aims to design an Android-based “Muhasabah Harian” application that enables users to conduct independent self-evaluation through a self-assessment approach. Development follows the Waterfall model, covering requirement analysis, design, implementation, testing, and support. Data were gathered through literature review, observation of similar applications, and interviews with teachers and students at SDN Panunggangan 2 Pinang. The system adopts the MVVM architecture, Jetpack Compose, and Kotlin. The application offers two modes: guest (offline) with local storage via Room Database and registered user (online) with storage in Firebase Firestore. Key features include reflection entry, evaluation history, progress graphs, and reminder notifications. The resulting application is expected to provide a practical and effective medium for daily self-reflection.